Intersection of Religions: Relations between Muslims and Non-Muslims in Tridana Mulia Village, Landono Sub-district, South Konawe Regency, Southeast Sulawesi Province - Akhmad Sukardi; Abd. Rasyid Masri; Suf Kasman; Arifuddin Tike (Jurnal Mamangan, 2023)
This study examines the harmony between religious communities in Tridana Mulia Village, Landono District, South Konawe Regency, Southeast Sulawesi, which is inhabited by Muslims, Christians, and Hindus. The purpose of the research is to describe the form of Muslim and non-Muslim relations in social life by emphasizing the aspect of harmony that exists in the midst of diversity. The research uses field research methods using phenomenological and sociological approaches. The results of the study show that harmony is built through positive interactions that are divided into daily relationships consisting of relationships between fellow Muslims and relationships with Muslims. Relations with non-Muslims are established in five main aspects: First, Economy, through the practice of buying and selling and business cooperation without religious discrimination; Second, Communication and social, through open dialogue, solidarity, and mutual cooperation; Third, Politics and government, with an inclusive and meritocratic pattern of political participation; Fourth, Education, through the implementation of multicultural education and religious moderation in schools; and Fifth, Culture, through joint celebrations, mutual cooperation, and respect for interfaith traditions. The associative relationship can be seen in the form of productive cooperation in cross-faith farmer groups. These findings confirm that differences in beliefs are not barriers, but rather a force to build social cohesion. The harmony created in Tridana Mulia Village can be a model for other multicultural regions in developing harmony, tolerance, and cooperation between religious communities.